Supernumerary Nipples, Congenital Scoliosis, Spina Bifida, Diastematomyelia, and Crossed Renal Ectopia in a child: Case Report of a Rare Combination - Panthee, Kiran; Sharma, Kiran; Kalakheti, Balkrishna (Journal of Lumbini Medical College, 2016)
Introduction: Supernumerary nipples are common anomalies which may be associated with several systemic disorders, particularly urinary tract abnormalities. Case report: Here we report a case of a 4½ year old male presenting to the pediatric out patient clinic with fever for three days and recurrent sinopulmonary infections. The child had supernumerary nipples over the right side with deformed thoracic cage, congenital scoliosis, diastematomyelia, crossed renal ectopia, and spina bifida. All the conditions present together did not match any syndrome reported till date. Conclusion: This was a rare syndrome and did not match fully with any known syndromes till date. This case warranted further investigation for its definite diagnosis but we do not have resources to that extent. DOI: https://doi.org/10.22502/jlmc.v3i2.74 J. Lumbini. Med. Coll. Vol 3, No 2, July-Dec 2015, Page: 55-57